Upaya Penanggulangan Pernikahan Dini Bagi Masyarakat di Desa Lawang Agung Kecamatan Kedurang Bengkulu Selatan - Histidiana, Veter; Dihamri; Zairin (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2024)
The focus of this research is to find out the efforts made by the community to overcome early marriage in Lawang Agung Village. Adapuan The aim of the research is to find out how efforts are made to overcome early marriage  in  Lawang  Agung  Village.  The  method  used  is  a  qualitative  method.  The  informants  that  the researcher took in This research consisted of ten people consisting of husband and wife couples who had legally entered into an early marriage, community leaders (village head, traditional leaders, religious leaders, village midwife)  and  the  community  in  Lawang  Agung  village.  Data  collection  was  carried  out  by  observation, interviews,  and  documentation.  The  data  obtained  was  analyzed  by  data  reduction,  data  presentation  and drawing conclusions. The research results show that the community in Lawang Agung Village has made various efforts  to  prevent  early  marriage  by  carrying  out  various  efforts,  such  as:  1.  Socialization  regarding  the negative effects of early marriage. Socialization has been carried out through youth posyandu. counseling about the health of childbearing age and the dangers of early marriage. However, socialization has not been carried out thoroughly. 2. Efforts to prevent early marriage for the community in Lawang Agung village.